2010
DOI: 10.1590/s1806-66902010000200009
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da demanda energética e desagregação do solo em diferentes sequências operacionais de preparo periódico

Abstract: Resumo -A correta seleção da sequência operacional do preparo do solo é fundamental para diminuir os custos da mecanização agrícola nas regiões que mobilizam intensamente o solo. Este trabalho teve como objetivo avaliar a demanda energética e a desagregação do solo em diferentes sequências operacionais de subsolagem e sistemas de preparo periódico do solo. O delineamento experimental utilizado foi em esquema fatorial 5x2 com 5 repetições, com blocos dispostos ao acaso, sendo 5 sistemas de preparo do solo (D -A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…According to Peloia and Milan (2010) and Salvador et al (2010), it is of fundamental importance under the conditions of intensive cultural practices and of farms occupying large areas to program operations with machines in the field in a rational manner for the efficient use of agricultural machinery and hand labor . Castro Neto (2001) observed that if a long series of meteorological data is available, it is important to conduct climatological studies by calculating the water balance in the soil and classifying the days as fit or unfit for various mechanized activities, types of soil and agricultural activities of interest.…”
Section: Introductionmentioning
confidence: 99%
“…According to Peloia and Milan (2010) and Salvador et al (2010), it is of fundamental importance under the conditions of intensive cultural practices and of farms occupying large areas to program operations with machines in the field in a rational manner for the efficient use of agricultural machinery and hand labor . Castro Neto (2001) observed that if a long series of meteorological data is available, it is important to conduct climatological studies by calculating the water balance in the soil and classifying the days as fit or unfit for various mechanized activities, types of soil and agricultural activities of interest.…”
Section: Introductionmentioning
confidence: 99%
“…The treatments which promoted the highest mean MWD values (0.91-0.95 mm) were only those with furrowing or subsoiling when compared to the other six treatments which used attachments promoting greater revolving (rotative hoe, disk harrow, leveling harrow, or moldboard plow). On the other hand, Salvador et al (2010) compared, in a dystrophic Red Nitosol with 510 g kg -1 clay, tilling with disk plow, disk plow + disk harrow, heavy harrow, heavy harrow + disk harrow, and scarifier; the authors concluded that the mean weight diameter was not statistically different, ranging from 5.26 to 8.51 mm. Pagliai et al (2004) reported that aggregates were less stable in plowed soils, resulting in a stronger tendency to form crusts than in soils treated with minimum tillage or subsoiling.…”
Section: Treatmentmentioning
confidence: 99%
“…According to SALVADOR et al (2010), to select the periodic tillage systems properly, we must take into account the energy demand and soil characteristics, such as texture and moisture. Greater knowledge and domains of these technologies may lead to reduced costs of crop production (KICHLER et al, 2007).…”
Section: Introductionmentioning
confidence: 99%